Ministry of tourism decree no. 549/2013 in connection with operation licenses to hotels and tourist establishments = قرار وزير السياحة رقم 549 لسنة 2013 تراخيص المنشآت الفندقية والسياحية - Egypt; The middle east library for economic services, translator. (2025)
Ministry of tourism decree no. 549 of the year 2013 issued on 21/7/2013 وزارة السياحة قرار رقم 549 لسنة 2013 صادر بتاريخ 21/7/2013